Bosnia and Herzegovina : Poverty Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The report consists of two volumes. The first volume contains the main Poverty Assessment report, integrating various data sources and inputs from local counterparts. The second volume provides an in-depth analysis of the Living Standards Measurement Survey (LSMS), jointly implemented by the Bank, and the Republika Srpska Statistical Institute (RSIS), the Federation of Bosnia and Herzegovina Statistical Institute (FIS), and the Bosnia and Herzegovina State Agency for Statistics (BHAS). This report presents the most comprehensive analysis of poverty in Bosnia-Herzegovina (BiH) to date, whose calculations suggest that poverty - defined as lack of adequate consumption - is quite substantial, affecting every fifth citizen. Poverty is substantial compared to some neighboring countries. Nevertheless, and despite the country's post-conflict situation and its low officially measured level of GDP, there is no extreme poverty. Inequality in material well-being also appears to be quite moderate by international standards and, the non-income dimensions of poverty are also generally not extreme in BiH. The analysis finds that a sizable proportion of the population faces the risk of falling into poverty, and it identifies risk factors that may thrust a non-poor household into poverty: a) precarious earning sources, because the predominant living arrangement features a single-earner household; b) widespread health risks, including uninsured financial risks, and lingering post-conflict risks; c) violation of human rights, discrimination and corruption; d) limited geographical mobility; e) limited access to formal safety nets; and, f) worn-out stock of household assets and limited access to credit. Physical security remains an issue, economic security is also a problem, and, powerlessness and voicelessness impede the capacity of poor people to break out of a vicious circle of impoverishment. To reduce poverty, selectivity, stability and growth are outlined, particularly focusing on prudent monetary policy, and responsible fiscal management.